2014
DOI: 10.2217/fon.14.163
|View full text |Cite
|
Sign up to set email alerts
|

On the Contribution of S100A10 and Annexin A2 to Plasminogen Activation and Oncogenesis: An Enduring Ambiguity

Abstract: Plasminogen receptors are becoming increasingly relevant in regulating many diseases such as cancer, stroke and inflammation. However, controversy has emerged concerning the putative role of some receptors, in particular annexin A2, in binding plasminogen. Several reports failed to account for the effects of annexin A2 on the stability and conformation of its binding partner S100A10. This has created an enduring ambiguity as to the actual function of annexin A2 in plasmin regulation. Supported by a long line o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…High levels of AnxA2 correlate with hyperfibrinolysis in acute promyelocytic leukemia (Flood and Hajjar, 2011;Luo and Hajjar, 2013). In addition, data from p11 KO mice support findings that AnxA2/p11-dependent plasmin generation is involved in tumor progression (Bharadwaj et al, 2013;Luo and Hajjar, 2013;Bydoun and Waisman, 2014).…”
Section: Anxa2 Ko Micesupporting
confidence: 63%
See 2 more Smart Citations
“…High levels of AnxA2 correlate with hyperfibrinolysis in acute promyelocytic leukemia (Flood and Hajjar, 2011;Luo and Hajjar, 2013). In addition, data from p11 KO mice support findings that AnxA2/p11-dependent plasmin generation is involved in tumor progression (Bharadwaj et al, 2013;Luo and Hajjar, 2013;Bydoun and Waisman, 2014).…”
Section: Anxa2 Ko Micesupporting
confidence: 63%
“…Different models of AnxA2/p11-mediated plasminogen activation have been proposed. We recommend several reviews that have extensively discussed the formation, structural organization, translocation and mode of action of the extracellular AnxA2/p11 complex (Flood and Hajjar, 2011;Grieve et al, 2012;Hedhli et al, 2012;Bharadwaj et al, 2013;Luo and Hajjar, 2013;Bydoun and Waisman, 2014).…”
Section: Anxa2 Ko Micementioning
confidence: 99%
See 1 more Smart Citation
“…Binding sites of the S100A10 proteins and t-PA have been identified in the N-terminal domain of annexin A2 at the amino acids residues 1-14 and 8-13, respectively (Kube et al 1992, Cesarman et al 1994. Recent data suggest that annexin A2 does not bind plasminogen directly but rather acts to transport S100A10 to the cell surface (Madureira et al 2011, Bydoun & Waisman 2014. Our findings suggest that the extracellular form of annexin A2 found in the cancer-associated stroma in the ovarian cancer tissues may represent a cleaved and secreted form of annexin A2, which may assist in ovarian cancer progression and metastasis.…”
Section: :11mentioning
confidence: 69%
“…The proteolytic cleavage of ECM proteins is regulated by protease receptors. Our research group has previously demonstrated that S100A10 (p11) is a receptor for the pro-protease plasminogen and can drive cancer cell invasion by mediating the conversion of plasminogen into the active protease, plasmin (Choi et al, 2003;Zhang et al, 2004;Phipps et al, 2011;Kwon et al, 2005;O'Connell et al, 2011;Madureira et al, 2012;Bydoun and Waisman, 2014). S100A10 binds to annexin A2 in the cytosol forming a heterotetrameric complex which then translocates to the cell surface (Madureira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%